Ethnobotanical investigation of medicinal plants of serawai tribe in Bengkulu as a potential of biology teaching materials - Prendi Niki Halhaji; I Gusti Putu Suryadarma (Universitas Negeri Jakarta, 2022)
The Serawai tribe is one of the indigenous tribes who live in the Bengkulu Province. The Serawai people still use medicinal plants because of the high trust of the Serawai people towards traditional medicine. Local plants have enormous potential to be developed as a source of learning biology. Therefore, the purpose of this study was to obtain information about the species of plants used by the Serawai tribal community in Tanjung Aur Village, Bengkulu as medicinal plants that have the potential as learning resources in biology learning at the high school level. The ethnobotanical studies covered include plant species, plant families, organs used, processing methods, and use value indexes (UV) for each plant. The ethnobotany study in this research used a qualitative descriptive-analytical method. Based on the results of the ethnobotanical study, there are 44 species of medicinal plants and 23 families. The most widely used plant part is the leaf with a percentage of 52.27%. The highest Use Value is Kaempferia galangal L from the Zingebareceae family. Based on the curriculum, the results of the investigation of medicinal plants can be used as teaching materials in biodiversity and plant topics for the grade of 10-th of high school. Teaching materials can form to be learning modules of medicinal plants.